Quality of life and general health in patients with temporomandibular disorders - Camila Maria Bastos Machado de Resende; Arthur César de Medeiros Alves; Lidiane Thomaz Coelho; João Carlos Alchieri; Ângelo Giuseppe Roncalli; Gustavo Augusto Seabra Barbosa (Brazilian Oral Research, 2013)
The aim of this study was to associate minor psychiatric disorders (general health) and quality of life with temporomandibular disorders (TMD) in patients diagnosed with different TMD classifications and subclassifications with varying levels of severity. Among 150 patients reporting TMD symptoms, 43 were included in the present study. Fonseca's anamnestic index was used for initial screening while axis I of the Research Diagnostic Criteria for Temporomandibular Disorders (RDC-TMD) was used for TMD diagnosis (muscle-related, joint-related or muscle and joint-related). Minor psychiatric disorders were evaluated through the General Health Questionnaire (GHQ) and quality of life was assessed using the World Health Organization Quality Of Life-Brief Version (WHOQOL-BREF). An association was found between minor psychiatric disorders and TMD severity, except for stress. A stronger association was found with mild TMD. Considering TMD classifications and severity together, only the item "death wish" from the GHQ was related to severe muscle-related TMD (p = 0.049). For quality of life, an association was found between disc displacement with reduction and social domain (p = 0.01). Physical domains were associated with TMD classifications and severity and the association was stronger for muscle and joint-related TMD (p = 0.37) and mild TMD (p = 0.042). It was concluded that patients with TMD require multiple focuses of attention since psychological indicators of general health and quality of life are likely associated with dysfunction.